FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH: KOMPETENSI SDM, STANDAR AKUNTANSI PEMERINTAHAN, DAN SISTEM AKUNTANSI KEUANGAN DAERAH - Sutri Handayani handa; Isnaini Anniswati Rosyida; Ana Fitriyatul Bilgies (PT. Jurnal Center Indonesia Publisher, 2025)
This research aims to examine the factors that influence the quality of regional government financial reports: human resources competency, government accounting standards, and regional financial accounting systems (empirical study of the Lamongan Regency Government and Bojonegoro Regency Government). This research was conducted in Lamongan and Bojonegoro involving 40 employees of BPKAD Lamongan and BPPKAD Bojonegoro as respondents. This quantitative research uses multiple linear regression. This technique is processed with SPSS 25 to analyze several hypotheses. The intercorrelation model between the three variables in this research reveals that human resource competency, implementation of government accounting standards and implementation of regional financial accounting systems have a significant correlation with the quality of regional government financial reports.